Recent advances in the use of CRISPR/Cas for understanding the early development of molecular gaps in glial cells - Barragán-Álvarez, Carla Patricia; Flores-Fernandez, José Miguel; Hernández-Pérez, Oscar R.; Ávila-Gónzalez, Daniela; Díaz, Nestor Fabian; Padilla-Camberos, Eduardo; Dublan-García, Octavio; Gómez-Oliván, Leobardo Manuel; Diaz-Martinez, Nestor Emmanuel (Frontiers in Cell and Developmental Biology, 2022)
Glial cells are non-neuronal elements of the nervous system (NS) and play a central role in its development, maturation, and homeostasis. Glial cell interest has increased, leading to the discovery of novel study fields. The CRISPR/Cas system has been widely employed for NS understanding. Its use to study glial cells gives crucial information about their mechanisms and role in the central nervous system (CNS) and neurodegenerative disorders. Furthermore, the increasingly accelerated discovery of genes associated with the multiple implications of glial cells could be studied and complemented with the novel screening methods of high-content and single-cell screens at the genome-scale as Perturb-Seq, CRISP-seq, and CROPseq. Besides, the emerging methods, GESTALT, and LINNAEUS, employed to generate large-scale cell lineage maps have yielded invaluable information about processes involved in neurogenesis. These advances offer new therapeutic approaches to finding critical unanswered questions about glial cells and their fundamental role in the nervous system. Furthermore, they better understand the significance of glial cells and their role in developmental biology.